2013
DOI: 10.1111/bpa.12103
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Brainstem Gangliogliomas Show BRAFV600E Mutation in a High Percentage of Cases

Abstract: Brainstem gangliogliomas (GGs) often cannot be resected, have a much poorer prognosis than those located in more common supratentorial sites, and may benefit from novel therapeutic approaches. Therapeutically-targetable BRAF c.1799T>A (p.V600E) (BRAFV600E) mutations are harbored in roughly 50% of collective GGs taken from all anatomical sites. Large numbers of pediatric brainstem GGs, however, have not been specifically assessed and anatomic- and age-restricted assessment of genetic and biological factors are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 25 publications
4
22
0
Order By: Relevance
“…GGs as previously reported by our group [15] showed that immunopositive cases manifesting stronger immunoreactivity in the ganglion cell component (Figure 4e) than the glial component, but never in the glial cell component alone. Indeed, the strong immunostaining in positive cases served to highlight the neoplastic ganglion cells, but in negatively mutated/negatively immunostained cases, both tumor components were equally negative (Figure 4f).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…GGs as previously reported by our group [15] showed that immunopositive cases manifesting stronger immunoreactivity in the ganglion cell component (Figure 4e) than the glial component, but never in the glial cell component alone. Indeed, the strong immunostaining in positive cases served to highlight the neoplastic ganglion cells, but in negatively mutated/negatively immunostained cases, both tumor components were equally negative (Figure 4f).…”
Section: Resultssupporting
confidence: 85%
“…After first demonstrating the principle that BRAF VE1 IHC might correlate with positive or negative Sanger sequencing in our original cohort [11], we extended our study to new cases of E-GBMs accrued since that publication as well as a subset of our original anaplastic pleomorphic xanthoastrocytomas (A-PXAs) which we had also previously assessed by Sanger sequencing, but not IHC [8]. We then compared the pattern of immunostaining we saw in these tumor types with our recently-published experience with gangliogliomas immunostained with the same antibody [15, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…The rate of positive PXA cases in our cohort was lower as previously reported, which might be explained by the fact that BRAF mutations are associated with a tumor location in the temporal lobe underrepresented in our cohort (Koelsche et al 2014). Likewise, there is an association with brainstem location in BRAF-V600E-positive GG in our group (Donson et al 2014). As expected from initial data of Schindler et al, all of our DNTs did not contain BRAF V600E mutations .…”
Section: Discussionsupporting
confidence: 50%
“…This leaves us to speculate that these tumors are inherently different, due to genetic or molecular characteristics. Rush et al, noted that brainstem GG are difficult to treat despite their low-grade pathological characteristics and suggested that this might be related to activating mutations in the BRAF gene 25,26 . To our knowledge, genetic differences between brainstem GG and those in other locations have not been described, but molecular signatures, such as BRAF mutations, or other yet to be defined genetic alterations, might provide insight into the survival trends observed in SEER.…”
Section: Discussionmentioning
confidence: 99%